Ongoing measles outbreak in Romania: Clinical investigation and molecular epidemiology performed on whole genome sequences - Robert Hohan; Marius Surleac; Victor Daniel Miron; Andreea Tudor; Ana-Maria Tudor; Oana Săndulescu; Ovidiu Vlaicu; Victoria Aramă; Daniela Pițigoi; Adriana Hristea; Anca Cristina Drăgănescu; Dimitrios Paraskevis; et al. (PLoS ONE, 2025)
Aim Romania is currently facing a prolonged measles outbreak. The aim of the study was to analyse the circulating human measles virus (HMV) strains by combining whole genome sequencing (WGS) with phylogenetic analysis, with a focus on the haemagglutinin gene. Methods We conducted an observational study in the first five months of 2024, in which 168 patients diagnosed with measles were randomly included. We have evaluated the clinical and epidemiological differences between children and adults. Screening for samples to be sequenced was performed with a commercial kit (PrimerDesign). WGS was done on Illumina MiSeq platform and phylogenetic analysis was performed with ML FastTree. Results No significant epidemiological and clinical differences between patients in the two age groups were identified. WGS was successfully performed for a number of 124 HMV strains. Genotype analysis indicated all the sequences as D8, except one that was B3. Phylogenetic analysis identified two well supported clusters, suggestive for at least two local transmission networks in Romania. One large transmission network (n = 108) consisted of sequences both from adults and children. Only one sequence from outside Romania (reported in Russia in 2023) clustered within this group. Another small transmission cluster was identified (14 sequences of which 11 from patients infected in the spring of 2024 and three in 2022). A few differences between the two co-circulating viral variants/clusters were observed. The median duration of hospitalisation was 2 days longer for patients in smaller cluster compared to those in the larger one (p = 0.019). Furthermore, these two clusters presented different mutation profiles in the hemagglutinin (HA) and neuraminidase (N) genes with implications for molecular surveillance. Conclusion The current measles epidemic in Romania is driven mainly by two D8 genotype variants with different mutation profiles and slightly different severity of the disease, highlighting the usefulness of sustained molecular surveillance.